VASCULAR ACCESS OPTIONS AT HEMODIALYSIS THERAPY INITIATION: COMPLICATIONS AND SURVIVAL OF PATIENTS WITH CHRONIC KIDNEY DISEAS STAGE 5 D - І.М. Shifris (Український Журнал Нефрології та Діалізу, 2016)
The annual increasing of dialysis population results tofocus world attention on the problems associated with improving of survival among patients with chronic kidney disease stage VD (CKD VD st.)., decreasing iatrogenic complicationfrequency. HD is the most common method ofrenal replacement therapy (RRT). Several studies haveproven the link between the type ofinitial vascular access, and an morbidity and survival of patients with CKD VD st..